The WACANA TOLERANSI BERAGAMA PADA UNGGAHAN AKUN TIKTOK @dasadlatifofficial: WACANA TOLERANSI BERAGAMA PADA UNGGAHAN AKUN TIKTOK @dasadlatifofficial - Christanty, Yuni Ayu (Kajian Moral dan Kewarganegaraan, 2023)
TikTok account @dasadlatifofficial belongs to a popular scholar in Indonesia namely Ustadz Dr. H. Das'ad Latif who is also a lecturer, businessman, and actively contributes da'wah to political and government agencies. In one of the uploads on the TikTok account, it discusses religious tolerance which has been seen by many users and received many responses from netizens in the comments column. This research focuses on how the discourse on religious tolerance is carried out by the owner of the TikTok account @dasadlatifofficial. The theory used in answering the formulation of the problem is Discourse theory put forward by Nourman Fairclough which views discourse as a social practice is part of society. This study uses the research method Critical Discourse Analysis (AWK) or Critical Discourse Analysis (CDA) with Nourman Fairclough's model. The data collection technique used was documentation which was analyzed using the Fairclough analysis model based on three dimensions namely Microstructural (Text Analysis), Mesostructural (Discourse Practice Analysis), and Macrostructural (Socio-Cultural Practice Analysis). The results of the study show that the discourse on religious tolerance carried by the @dasadlatifofficial account is that religious tolerance is an attitude that gives freedom to religious people without interfering with one another. Religious tolerance shows an attitude of respect for the existence of other different religions. Religious tolerance is also an attitude of accepting differences or commonly known as principles (agree in disagreement). Making discourse is based on Islamic ideology as a rationale and utilizing the development of the TikTok application as a means of dissemination. This also shows that religious people can also be good citizens, including in efforts to maintain unity in Indonesia Keywords: Critical Discourse Analysis, Religious Tolerance, Social Media.